Reconstructing Ta’dib Philosophy: A Theoretical Framework for Modern Islamic Boarding School System - Anwar, Heru Saiful; Zarkasyi, Hamid Fahmy; Muslih, Mohammad; Laila, St. Noer Farida (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study explores the philosophy of Ta’dib as the foundational framework for the Islamic education system, emphasizing moral and character development alongside intellectual growth. This research employed a literature review method by analyzing classical and contemporary sources to explore key Islamic educational concepts' meanings, implications, and differences, including tarbiyah, ta’lim, and Ta’dib. Through a comprehensive examination of relevant books, journal articles, and scholarly works, the study identified Ta’dib as a holistic concept emphasizing moral and character development in Islamic education. The findings reveal that Ta’dib extends beyond formal education by cultivating individuals with noble morals, ethical conduct, and a deep understanding of Islamic values. Unlike tarbiyah and ta’lim, which focus on knowledge transfer and spiritual development, Ta’dib serves as a comprehensive moral compass for shaping character and guiding behavior. The study highlights the relevance of Ta’dib in addressing contemporary educational challenges, particularly in nurturing ethical leadership and fostering community cohesion. Quranic schools embody Ta’dib-based education and are exemplary models of integrating character formation with Islamic teachings. This research concludes that the philosophy of Ta’dib provides a sustainable and effective framework for Islamic education. It recommends that educational institutions adopt Ta’dib-centered curricula to address students' moral, spiritual, and intellectual needs, ensuring they become responsible individuals who embody Islamic principles daily.